Editorial board, information for authors, and other front matter - Jason D. Ellis (Journal of Applied Communications, 2015)
This content includes the front cover, the table of contents, editorial and other information for authors for vol. 99, no. 4 (2015) of Journal of Applied Communications
Keywords: masthead